Accounting Issues Related to Market Risks of Loan Products - Traian Cristin Nicolae (Ovidius University Annals: Economic Sciences Series, 2019)
This scientific paper aims at an empirical study of some brief aspects of credit in the current stage of the Romanian economy . A potential reduction in population lending in Romania is believed to have a huge impact on consumption, production , investments and on the state budget. Thus, a 10 % reduction in amounts of credits will have a negative impact on GDP of 4 %. The new draft laws allow the creation of a space of unconfirmed provisions. All these proposals come with losses for the banking industry, including image, and, paradoxically, is happening in the Romania where financial intermediation occupies a low level - more than a quarter - 26.4%. The large differences in the regulatory laws adopted by the Member States contribute to the differences in the flows of the European market .